Collaborative Governance Dalam Pelaksanaan Grebeg Suro Ponorogo Tahun 2024 - Rifqi Putra Al Ghifari; Sri Wibawani (Universitas Muhammadiyah Ponorogo, 2026)
Grebeg Suro Ponorogo is a cultural preservation program that becomes an annual celebration in Ponorogo Regency. In its implementation, Grebeg Suro Ponorogo is supported by the APBD budget, which in 2024 experienced a decrease in the budget, making the Ponorogo Regency Culture, Tourism, Youth and Sports Office collaborate with private parties to cover the existing budget shortfall. The purpose of this study, namely to describe and describe the collaborative governance process in the Implementation of Grebeg Suro Ponorogo in 2024. This research uses a descriptive qualitative type with the technique of determining informants through purposive sampling and snowball sampling. The data collection technique was carried out by combining three methods, namely observation, interviews, and documentation which were analyzed using the interactive analysis model belonging to. The collaborative governance model was analyzed using the theory (Ansell & Gash, 2008) including initial conditions, institutional design, leadership, collaboration process. The results showed that the collaboration that exists in Grebeg Suro Ponorogo has been running well between the Ponorogo Regency Culture, Tourism, Youth, and Sports Office and PT Local Hero Motivation. Keyword: Collaborative Governance; Cultural Preservation; Grebeg Suro Ponorogo;